Use of combination of satins as antagonists of SPARC in stomach cancer: an in silico study - Rashed, Sadman Sakib Bin (Brac University, 2019)
This project report is submitted in partial fulfilment of the requirements for the degree of Bachelor of Pharmacy, 2019.